Eigenvalue Solver for Fluid and Kinetic Plasma Models in Arbitrary Magnetic Topology. (22nd June 2016) - Baver, D. A.; Myra, J. R.; Umansky, M. V.
Abstract: ArbiTER (Arbitrary Topology Equation Reader) is a new code for solving linear eigenvalue problems arising from a broad range of physics and geometry models. The primary application area envisioned is boundary plasma physics in magnetic confinement devices; however ArbiTER should be applicable to other science and engineering fields as well. The code permits a variable numbers of dimensions, making possible application to both fluid and kinetic models. The use of specialized equation and topology parsers permits a high degree of flexibility in specifying the physics and geometry.